2013
DOI: 10.3800/pbr.8.74
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon-driven variations in primary production and phytoplankton assemblages in Sagami Bay, Japan: A case study of typhoon Mawar (T0511)

Abstract: Climate change has the potential for intensification of typhoons, which will cause stronger effects on aquatic ecosystems in the future. The effect of typhoon Mawar (T0511), passing Manazuru Port located in the western part of Sagami Bay, Japan, was investigated from August to September 2005. Immediately after the passage of Mawar, photosynthetically available radiation showed high values, salinity decreased dramatically and nutrient concentrations (NO 2 +NO 3 , PO 4 and Si(OH) 4 ) increased. Skeletonema spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…According to path of Typhoon Chaba, phytoplankton primary production was significantly increased in Korean coastal waters during the autumn. The increased levels of nutrients in coastal waters can have a significant impact on annual primary production [11] and can determine phytoplankton community structure [19,20]. In this study, an increase in precipitation due to Typhoon Chaba during the two weeks led to an elevation of the Nakdong River discharge, resulting in nutrients loading to the nearby coastal waters; there were significant negative relationships between salinity and nutrients at Zone III (NO 2 + NO 3 , r = -0.92, p < 0.001; NH 4 , r = −0.72, p < 0.001; PO 4 , r= −0.95, p < 0.001; and SiO 2 , r = −0.94, p < 0.001), implying that the abundant nutrients from the river discharge were supplied to Zone III and remained present even 2 weeks after the typhoon.…”
Section: Relationship Of Phytoplankton Bloom With High Nutrient Levelmentioning
confidence: 99%
“…According to path of Typhoon Chaba, phytoplankton primary production was significantly increased in Korean coastal waters during the autumn. The increased levels of nutrients in coastal waters can have a significant impact on annual primary production [11] and can determine phytoplankton community structure [19,20]. In this study, an increase in precipitation due to Typhoon Chaba during the two weeks led to an elevation of the Nakdong River discharge, resulting in nutrients loading to the nearby coastal waters; there were significant negative relationships between salinity and nutrients at Zone III (NO 2 + NO 3 , r = -0.92, p < 0.001; NH 4 , r = −0.72, p < 0.001; PO 4 , r= −0.95, p < 0.001; and SiO 2 , r = −0.94, p < 0.001), implying that the abundant nutrients from the river discharge were supplied to Zone III and remained present even 2 weeks after the typhoon.…”
Section: Relationship Of Phytoplankton Bloom With High Nutrient Levelmentioning
confidence: 99%
“…Local storms in ice‐free regions of the Arctic Ocean may generate profound inertial motion in the upper water and enhance interior mixing, causing turbulent energy levels to increase to levels comparable to those in lower latitude seas [ Rainville and Woodgate , ]. In such seas, field studies of the passage of typhoons have suggested that ecosystem responses start with episodic nutrient loading, followed by sizable diatom blooms, intense grazing pressure, and a significant carbon flux [ Chang et al ., ; Hung and Gong , ; Chung et al ., ; Tsuchiya et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…These hurricane-induced blooms can occur even in waters that are normally oligotrophic, and thus may be an important contributor to new primary production in these sparse ecosystems (Babin et al 2004). Studies have suggested that hurricane-induced blooms may account for 20-30% of new production, and a single hurricane event can increase primary production by an order of magnitude (Lin et al 2003, Tsuchiya et al 2013. These hurricane-induced blooms are rarely considered in calculations of air-sea carbon flux, and may be an important contributor (Mahadevan et al 2011).…”
Section: Introductionmentioning
confidence: 99%